'This anguish, like a kind of intimate song' : resistance in women's literature of World War II - Westerfield, L. Leigh (Lillian Leigh), 1954- (Internationale Forschungen zur allgemeinen und vergleichenden Literaturwissenschaft, 2004)
The romanticized image of the heroic male resistance fighter in World War II belies a truth that is both darker and more personal. This literary history explores, for the first time, the reality of European women's roles in fighting Nazism. By comparing the resistance literature of French and German authors-both famous and more obscure-this innovative book links the traditional gender expectations for women and the conventions of their everyday lives with their unique forms of resistance. Theirs was an opposition grounded in the ordinary, beyond the sphere of political violence. Women were long regarded as outsiders to combat and politics, with no stake in upholding resistance myths. Women authors therefore freely rendered the personal and moral landscape of the resister's world in a new vocabulary. They revised standard rhetoric and replaced heroism and bullets with the values of home, human relationships, and candid acknowledgement of the sorrow, fear, and uncertainty of war. A groundbreaking study for students of European history, women's studies, peace studies, or comparative literature, this volume is also accessible to a general audience interested in the role of women in World War II.